MONITORING OF SUBJECTS AND FINANCIAL AND ECONOMIC ACTIVITY ENVIRONMENT - M. Kolesnikov; D. Motrenko (Вестник университета)
The category “monitoring” of subjects of financial and economic activity are analized. In particular the following notions have been researched: indicative, representational, retrospective, current and perspective monitoring. It was suggested that the work of the bank is to be assessed based not on specified indexes dynamics but based on bank location change in a competitive environment and apply cenology analysis for assessment of the influence of market environment.